AgNPs (at) Co (II) MOFs (at) PtNPs nano composite material and electrode and application thereof

By using electrochemical biosensors modified with AgNPs@Co(II)MOFs@PtNPs nanocomposites, the lack of high sensitivity and specificity of rabies diagnosis in the prior art is solved, and rapid, sensitive and specific detection of rabies nuclear protein antibodies is achieved.

CN119857849APending Publication Date: 2025-04-22CHONGQING UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510086171.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

There is a lack of high sensitivity, rapid and specific rabies diagnosis methods in the prior art, especially in the detection of rabies nuclear protein antibodies.

Method used

AgNPs@Co(II)MOFs@PtNPs nanocomposites were used to modify the glass carbon electrode, and an electrochemical biosensor was constructed to achieve rapid detection of rabies nuclear protein antibodies through electrochemical detection methods.

Benefits of technology

This method realizes high sensitivity detection of rabies antibodies, has a wide detection range and good selectivity, and provides a simple, fast, high sensitivity and strong specificity detection method, which has great clinical application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857849A_ABST
    Figure CN119857849A_ABST
Patent Text Reader

Abstract

The invention discloses an AgNPs (at) Co (II) MOFs (at) PtNPs nano composite material and an electrode and application thereof, the AgNPs (at) Co (II) MOFs (at) PtNPs nano composite material is prepared by the following steps: preparing Co (II) MOFs (at) PtNPs by a mixed solvothermal method, then adsorbing AgNPs on the surface of the Co (II) MOFs (at) PtNPs to form the AgNPs (at) Co (II) MOFs (at) PtNPs nano composite material, modifying a glassy carbon electrode by the obtained material, constructing an electrochemical biosensor, and applying the electrochemical biosensor to detection of a rabies antibody. The electrochemical sensor has an extremely low detection lower limit and a relatively wide detection range, and can specifically recognize the rabies antibody. Therefore, the sensor provides a simple, convenient, rapid, high-sensitivity and high-specificity detection method for rabies diagnosis, and has great application value and development potential in clinical medicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical detection, in particular to an AgNPs@Co(II)MOFs@PtNPs nanocomposite material, and also to an electrode made from the material and applications thereof. Background Art

[0002] Rabies is a fatal encephalitis disease caused by the rabies virus (RABV) that is common to both humans and animals. Patients mainly suffer from central nervous system lesions. It is the most widespread and serious zoonotic infectious disease in the world, with a mortality rate of almost 100%. In particular, the outbreak of rabies in countries around the world in the mid-20th century caused a large number of deaths in humans, giving rabies great public health significance.

[0003] Rabies virus belongs to the genus Lyssavirus of the family Rhabdoviridae. It is a bullet-shaped virus with a helical symmetric nucleocapsid and an envelope on the surface. It contains single-stranded RNA and is the pathogen that causes rabies. Rabies virus has two main antigens: one is the glycoprotein antigen (GP) on the outer membrane of the virus, which can bind to the acetylcholine receptor to make the virus neurotoxic and produce neutralizing antibodies and hemagglutination-inhibiting antibodies in the body. Neutralizing antibodies have a protective effect; the other is the nucleoprotein antigen (NP) on the inner layer, which can produce complement-binding antibodies and precipitins in the body, but has no protective effect. Of the two antigens, the most studied is the glycoprotein, while the research on the nucleoprotein is relatively limited. It is usually limited to understanding that it is the structural protein with the highest expression, best stability and most conserved sequence among the RABV structural proteins, and is used for virus typing and diagnosis. However, in recent years, studies have found that the nucleoprotein is closely related to the virulence and pathogenicity of the virus, and plays an important role in the body's antiviral infection. In addition, the nucleoprotein can be used in the diagnosis, vaccine development and prevention and treatment of rabies.

[0004] Nanobodies (Nbs) are naturally missing variable regions of the light chain and the first constant region (CH1) of the heavy chain, which exist in camelids or sharks. Due to their small size and single-domain format, nanobodies have a larger binding surface and lower nonspecific background binding. Compared with traditional antibodies, nanobodies have many characteristics: (1) strong tolerance; (2) single-domain structure, easy to modify; (3) mutations in hydrophilic amino acids, easy soluble expression, easy to produce, and reduced production costs. In summary, the preparation of nanobodies based on rabies NP protein as a target provides a tool for the diagnosis and treatment of rabies.

[0005] In recent years, the number of deaths due to rabies has always ranked first among the legally reportable infectious diseases in my country, and it is a major epidemic disease that seriously endangers my country's public health. Vaccination is the most effective means to control the occurrence and spread of animal rabies, and the use of effective diagnostic methods to evaluate the immune effect of animals immunized with rabies virus vaccines is the primary issue to be solved to ensure the safety of humans and animals. Therefore, it is of great significance to study rapid, simple, highly sensitive and specific rabies diagnostic methods.

[0006] Electrochemical immunosensor is a labeling immunoassay method that combines immunotechnology with electrochemical detection. It is based on antigen-antibody specific reactions, converts the biological response signal after the antigen / antibody reaction reaches equilibrium into a measurable electrical signal and derives it through the base electrode. When measured by electrochemical detection method, the signal size is linearly related to the target analyte within a certain concentration range, thereby realizing the analysis and determination of the target detection object. Electrochemical detection methods are convenient and simple to operate, respond quickly and have high selectivity. They are widely used in food safety control, environmental testing and pharmaceutical analysis. There are few reports on the electrochemical detection of rabies N protein. Metal-organic framework materials (MOF) are organic-inorganic hybrid solid crystalline materials with a three-dimensional grid structure formed by self-assembly of inorganic metal ions or clusters and organic ligands through coordination bonds. Metal-organic frameworks (MOFs) composed of inorganic ions and polyhedral organic ligands show various potential applications such as luminescence, sensors, drug delivery and catalysis because of their inherent large surface area, uniform but adjustable cavities, and customizable chemical reactions. Compared with their main counterparts, functionalized MOFs or MOF-based materials show more defined characteristics and even novel properties. In the field of electrochemistry, Co(II)MOFs materials show good performance with advantages such as structural diversity, stability and controllability. Bimetallic MOF materials (AgNPs@Co(II)MOFs@PtNPs) usually have a very high specific surface area, so they can provide a large number of surface active sites for the adsorption of antigens and antibodies. Using rabies virus (RABV) nucleoprotein RV NP antigen and antibody as reagent raw materials, an RV NP antibody electrochemical biosensor detection method based on AgNP@Co(II)MOFs@PtNP material modified glassy carbon electrode was initially established, providing a new detection technology for the diagnosis of rabies. Summary of the invention

[0007] In view of this, one of the objects of the present invention is to provide a AgNPs@Co(II)MOFs@PtNPs nanocomposite material, a second object of the present invention is to provide the use of the AgNPs@Co(II)MOFs@PtNPs nanocomposite material in the preparation of an electrochemical biosensor; a third object of the present invention is to provide an electrochemical biosensor containing the AgNPs@Co(II)MOFs@PtNPs nanocomposite material; a fourth object of the present invention is to provide an electrochemical workstation constructed using the electrochemical biosensor; and a fifth object of the present invention is to provide a method for detecting rabies antibodies using the electrochemical biosensor.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] 1. AgNPs@Co(II)MOFs@PtNPs nanocomposite material, wherein the AgNPs@Co(II)MOFs@PtNPs nanocomposite material is prepared by a mixed solvent thermal method to prepare Co(II)MOFs@PtNPs, and then AgNPs are adsorbed on the surface of Co(II)MOFs@PtNPs to form the AgNPs@Co(II)MOFs@PtNPs nanocomposite material.

[0010] Preferably, the preparation method of the Co(II)MOFs@PtNPs is as follows: first, slowly add a sodium citrate aqueous solution to a solution containing H2 PtCl6, react until the solution turns dark brown, and obtain PtNPs with a size of 250 nm, then add the synthesized PtNPs to a mixture containing DMF and ethanol, and then add a DMF solution containing CoSO4·7H2O and NH2-H2BDC, ultrasonically treat for 30 minutes, heat at 100°C for 36 hours, and collect the product by centrifugation to obtain Co(II)MOFs@PtNP.

[0011] Preferably, in the present invention, the AgNPs are adsorbed on the surface of Co(II)MOFs@PtNPs by adding AgNPs with an average size of 500 nm to Co(II)MOFs@PtNPs, stirring the reaction for 12 hours, and centrifuging the mixture to obtain the AgNPs@Co(II)MOFs@PtNPs nanocomposite material.

[0012] 2. Application of the AgNPs@Co(II)MOFs@PtNPs nanocomposite material in the preparation of electrochemical biosensors.

[0013] 3. An electrochemical biosensor containing the AgNPs@Co(II)MOFs@PtNPs nanocomposite material, wherein the electrochemical biosensor is cleaned by a glassy carbon electrode, and then the glassy carbon electrode rod is grinded in sequence with a-alumina polishing powder with particle sizes of 1.0 μm, 0.5 μm, and 0.05 μm and water, and then the ultrasonically treated AgNPs@Co(II)MOFs@PtNPs composite material suspension is dropped into the center of the glassy carbon electrode rod and dried to obtain an AgNPs@Co(II)MOFs@PtNPs working electrode.

[0014] 4. An electrochemical workstation constructed using the electrochemical biosensor.

[0015] Preferably, the equipment required for building the platform is an electrochemical sensing experimental platform consisting of an electrochemical workstation (ZAHNERPP211, Germany), an electrolyte cell, and a Thales-XT electrochemical output analysis. A glassy carbon electrode is connected to an electrolytic cell to form a three-pole electrode system (working electrode, counter electrode, reference electrode). The material modified on the electrode surface is combined with a macromolecular antibody, and the biological signal is converted into an electrical signal through the electrochemical workstation.

[0016] 5. The method of detecting rabies antibodies using the electrochemical biosensor is as follows: adding rabies nucleoprotein antigen to the electrochemical biosensor, and the carboxyl group of the nucleoprotein antigen undergoes dehydration condensation with the hydroxyl group on the AgNPs@Co(II)MOFs@PtNPs material to be fixed to the electrode, and a skim milk powder solution is used as a blocking liquid to block the unbound active sites, and then the sample to be tested is placed incubated, and rapid detection of rabies antibodies is achieved based on the induced current on the electrode.

[0017] The beneficial effects of the present invention are as follows: the present invention prepares Co(II)MOFs@PtNPs by a mixed solvent thermal method, which is composed of internal Pt nanoparticles (PtNPs) encapsulated by amino-functionalized Co(II)MOFs materials. Subsequently, AgNPs are adsorbed on the surface of Co(II)MOFs@PtNPs to form AgNPs@Co(II)MOFs@PtNPs nanocomposite materials, and the successfully synthesized AgNPs@Co(II)MOFs@PtNPs are used to modify the glassy carbon electrode, and the electrochemical biosensor is applied to the detection of RC NP antibodies. The composite material AgNPs@Co(II)MOFs@PtNPs enables the rabies antibody electrochemical biosensor to have good selectivity and a wide detection range. Therefore, the sensor provides a simple, rapid, highly sensitive and specific detection method for rabies diagnosis, and has great application value and development potential in clinical medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0019] Figure 1 SEM scanning electron microscopy (morphology) of AgNPs@Co(II)M0Fs@PtNPs composite materials (a: SEM electron microscopy image of AgNPs at 500nm; b: SEM electron microscopy image of PtNPs at 500nm; c: SEM image of Co(II)MOFs@PtNPs at 1μm; d: SEM electron microscopy image of AgNPs@Co(II)M0Fs@PtNPs at 5μm);

[0020] Figure 2 EDS element mapping of AgNPs@Co(II)M0Fs@PtNPs composite material;

[0021] Figure 3 The electrochemical principle diagram (a: the preparation process of AgNPs@Co(II)MOFs@PtNPs; b: the process of modifying the glassy carbon electrode with electrode materials);

[0022] Figure 4 Modified CV curve for electrode;

[0023] Figure 5 is the EIS curve of electrode modification;

[0024] Figure 6 ELISA kit for rabies clinical samples (corresponding data are shown in Table 2);

[0025] Figure 7 DPV curves at different RV NP antibody concentrations;

[0026] Figure 8 It is the linear relationship under different RV NP antibody concentrations;

[0027] Fig. 9 This is a repeatability experiment within the sensor group (the same electrode rod detects different samples);

[0028] Fig.10 This is a repeatability experiment between sensor groups (different electrodes detect the same sample);

[0029] Fig.11 For sensor stability experiment;

[0030] Fig.12 is the sensor-specific experimental current change;

[0031] Fig.13 It is the current change of the sensor in clinical experiments. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0033] The chemical reagents used in the experiments of the present invention were of analytical grade, and the working solution was prepared with ultrapure water. Chloroplatinic acid (H2PtCl6) and cobalt sulfate heptahydrate (CoSO4·7H2O) were purchased from Chongqing Platinum Strontium Titanium Technology Co., Ltd. Sodium citrate, polyvinylpyrrolidone (PVP), N,N-dimethylformamide (DMF), 2-aminoterephthalic acid (NH2-H2BDC), and silver nitrate (AgNO3) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. Potassium chloride (KCl), sodium chloride (NaCl), and ethanol were purchased from Chongqing Chuandong Chemical (Group) Co., Ltd. EDC, MES solution, and N-hydroxysuccinimide (NHS) were purchased from Aladdin Holding Group Co., Ltd. Potassium ferrocyanide K3[Fe(CN)6] and potassium ferrocyanide K4[Fe(CN)6] were purchased from Shanghai Aladdin. Anhydrous disodium hydrogen phosphate, anhydrous potassium dihydrogen phosphate, and potassium chloride were purchased from Chengdu Cologne Chemical Co., Ltd. 0.01 M PBS (0.137 M NaCl, 0.0027 M KCl, 0.01 M anhydrous disodium hydrogen phosphate, 0.002 M anhydrous potassium dihydrogen phosphate, dilute to 1 L, pH 7.4).

[0034] Rabies virus NP antigen (RV-NP Ag), rabies virus antibody (RV-NP Ab), toxoplasma gondii antibody (TG Ab), foot-and-mouth disease antibody (FMDV Ab), Brucella antibody (LPS Ab), canine distemper antibody (CDV Ab) were self-made, and rabies positive serum ELISA kit and clinical sample serum were provided by Chongqing Animal Disease Control Center. A total of 24 serum samples from dogs were collected. The serum sample detection work involved in this experiment has been approved by the Medical Ethics Committee of Chongqing University of Technology. The three-electrode system comes from Shanghai Yueci Electronic Technology Co., Ltd., which consists of a glassy carbon electrode working electrode (3mm), a silver / silver chloride reference electrode (R0303), a platinum sheet electrode countercurrent electrode (10×10×0.1mm) and a 5mM potassium ferrocyanide solution non-sealed electrolytic cell.

[0035] Example 1. Preparation of AgNPs@Co(II)MOFs@PtNPs

[0036] (1) Synthesis of PtNPs

[0037] Synthesize PtNPs with an average size of about 250nm. 6mL of 1% sodium citrate aqueous solution was slowly added to a boiling mixture solution containing 1mL of H2 PtCl6 solution (1% w / w) and 40mL of water and kept at this temperature for about 40min. After cooling to room temperature, the resulting solution gradually turned dark brown, indicating that PtNPs were successfully formed.

[0038] (2) Synthesis of Co(II)MOFs@PtNPs

[0039] Co(II)MOFs@PtNPs were prepared following the method reported in the literature with minor modifications. First, 1.6 g of PVP was dissolved in a mixture containing DMF (36 mL) and ethanol (24 mL). Then, 0.6 mL of the synthesized PtNPs was slowly added to the above mixture. Then, 12 mL of DMF containing 0.13095 g of CoSO4·7H2O and 0.03258 g of NH2-H2 BDC was added to the above solution and ultrasonicated for 30 min. The resulting solution was heated at 100 °C for 36 h in a polytetrafluoroethylene-lined autoclave. The product was collected by centrifugation at 4000 rpm for 10 min and redispersed in 16 mL of ethanol. Finally, Co(II)MOFs@PtNPs were obtained by centrifugation, and the process was repeated twice to remove the unreacted chemical reagents.

[0040] (3) Synthesis of AgNPs

[0041] Synthesize AgNPs with an average size of about 500nm. First, 0.1g of silver nitrate (AgNO3) was dissolved in ultrapure water and placed in a double-necked round-bottom flask filled with 100ml of distilled water, and kept boiling for 15min. Then, 5ml of sodium citrate solution (1%) was added to the above mixture, and 1ml was added every 5min. The solution changed color to bright yellow. After continuous heating and stirring for 15min, the solution was cooled to room temperature.

[0042] (4) Preparation of AgNPs@Co(II)MOFs@PtNPs

[0043] 1 mL of the as-synthesized AgNPs solution was added to the above Co(II)MOFs@PtNPs and stirred at room temperature for 12 hours. The mixture was then centrifuged at 4000 rpm for 8 min to obtain the AgNPs@Co(II)MOFs@PtNPs nanocomposite. The prepared nanocomposite was stored in PBS until use.

[0044] The morphology of the AgNPs@Co(II)M0Fs@PtNPs composite was scanned by SEM during its preparation. Figure 2As shown in (a)-(d). Figure 2 The SEM results of (a) and 2(b) show that the prepared materials are nanoparticles with unique spherical nanostructures. Figure 2 (c) is Co(II)MOFs@PtNPs, which presents a sharp kidney shape with certain curves and curvatures, and there are protruding particles on the surface, indicating that the nanometal particles PtNPs are encapsulated in Co(II)MOFs. After AgNPs were fixed (2d), Co(II)MOFs@PtNPs were surrounded by many nanoparticles and the surface became smooth, indicating that AtNPs have been successfully loaded onto the surface of Co(II)MOFs@PtNPs, forming an AgNPs@Co(II)MOFs@PtNPs composite with a large surface area and three-dimensional structure. In order to evaluate the elemental composition and distribution of the AgNPs@Co(II)MOFs@PtNPs composite, the energy dispersive X-ray spectroscopy (EDS) of AgNPs@Co(II)MOFs@PtNPs was performed. From the element mapping of the AgNPs@Co(II)M0Fs@PtNPs composite material, it can be seen that there are six elements, Ag, Pt, Co, F, N, and O, on the surface of the composite material, and the six elements are evenly distributed ( Figure 2 , (a)-(f) and Table 1). These results indicate that the composite material was successfully synthesized.

[0045] Table 1. Element content distribution of composite materials

[0046]

[0047] Example 2: Construction of electrochemical biosensor

[0048] First, clean the glassy carbon electrode, usually wipe it with anhydrous ethanol cotton ball. If it is still not clean, use a-alumina polishing powder with a particle size of 1.0μm, 0.5μm, and 0.05μm, add water to grind the glassy carbon electrode rod in turn, and wash it with water. The material synthesized in Example 1 is modified as follows: After the AgNPs@Co(II)MOFs@PtNPs composite material suspension is ultrasonically treated for 30 minutes, it is added dropwise to the center of the glassy carbon electrode rod and dried at 55°C to obtain the AgNPs@Co(II)MOFs@PtNPs working electrode. In order to determine whether the constructed sensor is successful, it is necessary to detect and record the changes in the induced current of each step of material modification through the electrochemical workstation cyclic voltammetry (CV), and use the electrochemical impedance spectroscopy (EIS) to study the relationship between the AC impedance and the frequency. The working principle diagram of the electrochemical sensor is shown in the figure Figure 3 shown.

[0049] Example 3: Sensor detection performance test

[0050] AgNPs@Co(II)MOFs@PtNPs material solution was added to the bare glassy carbon electrode for sensor modification. The carboxyl group of the RV NP antigen was fixed to the sensor by dehydration condensation with the hydroxyl group on the material. A 5% skim milk powder solution prepared with PBS was used as a blocking solution to block the unbound active sites. RV NP antibody samples with different concentrations were detected and incubated for 30 minutes. During this period, the antigen and antibody would undergo a specific binding immune reaction. The electrochemical system adopted a three-electrode system, with a platinum electrode as the counter electrode and a silver chloride electrode as the reference electrode. The measurement was carried out at 5mM [Fe(CN)6] 3- / 4 The modification of the working electrode was verified by CV and EIS methods. The scanning range of CV was -0.6 to 1.0 V vs. Ag / AgCI, and the scanning rate was 50 mVs -1 , the low frequency and high frequency of EIS are 0.01Hz and 10kHz respectively. With the help of an electrochemical workstation (the electrochemical workstation was purchased from ZAHNERPP211 in Germany, and the electrolyte components added to the electrolyte cell are: potassium ferrocyanide solution (5mM): 1.6462g potassium ferrocyanide, 1.8417g potassium ferrocyanide, 7.4551g potassium chloride were weighed on a balance and added to an appropriate amount of 0.1M PBS, mixed evenly, fixed to 1L, stored at room temperature, and analyzed using Thales-XT electrochemical software) to detect the induced current on the electrode, thereby achieving rapid detection of rabies antibodies. The results are as follows Figure 4As shown. The results show that the redox peak current of bare GCE is low (curve GCE), AgNPs and PtNPs are metal nanoparticles with high conductivity, and the redox peak current increases (curves AgNPs and PtNPs). Since the synthesized Co(II)M0Fs@PtNPs contains MOF materials, the conductivity is poor. After Co(II)M0Fs@PtNPs is fixed on the GCE electrode, the redox peak current is slightly lower than that of PtNPs (curve Co(II)M0Fs@PtNPs). Therefore, in order to increase the peak current, AgNPs are introduced to increase the redox peak of the sensor. It can be seen from the curve that the addition of AgNPs can greatly increase the peak current (curve AgNPs@Co(II)M0Fs@PtNPs). The bimetallic MOF material (AgNPs@Co(II)MOFs@PtNPs) has a very high specific surface area and can greatly enhance the conductivity. After being activated by EDC / NHS, the amino groups on the composite material can effectively bind to the carboxyl groups on the RV NP antigen to form an amide bond. It can be seen from the curve that the redox peak current after binding to the antibody has decreased significantly. This is because their RV NP antigen is essentially composed of covalent bonds. When they are modified on the material, the electron transfer rate decreases and the peak current decreases, indicating that the antigen modification is successful (curve AgNPs@Co(II)M0Fs@PtNPs-Ab). After being blocked with milk powder solution, the peak current continues to decrease, indicating that the antigen blocking is successful (curve AgNPs@Co(II)M0Fs@PtNPs-Ab-Milk). After the blocking is completed, the electrode further reacts with the RV NP antibody solution, and the peak current also continues to decrease (curve AgNPs@Co(II)M0Fs@PtNPs-Ab-Milk-Ag). Since a new immune complex is formed after the antigen-antibody reaction, the electron transfer is further hindered. In summary, the sensor is successfully prepared and can be further applied to RV-NP antibody detection and performance analysis. EIS is used to study the relationship between the electrochemical AC impedance and the frequency. The Nyquist plot measured by this method can be fitted to the effective impedance of the electrode. The results are as follows: Figure 5 shown.

[0051] Example 4: Electrochemical analysis

[0052] (1) Sensitivity test

[0053] 24 clinical sera were tested with a rabies positive serum ELISA kit, and the sera with negative test results were used to calculate the critical value of the sensor. RV NP antigen was fixed on the working electrode, and a 5% skim milk powder solution was prepared with PBS as a blocking solution. After blocking for 1 hour, rabies antibody solutions diluted with PBS (1pg / mL, 5pg / mL, 10pg / mL, 50pg / mL, 100pg / mL, 500pg / mL, 1ng / mL, 10ng / mL, 500ng / mL, 550ng / ml, 600ng / ml) were added dropwise, incubated at room temperature for 30 minutes, and tested using differential pulse voltammetry (DPV), with a scanning voltage of -0.1V to +0.5V, and the data was recorded. The results are shown in Figure 2. Figure 6 As shown in Table 2, there are 8 positive sera and 16 negative sera. The prepared working electrode was placed in 16 negative canine sera for incubation, and the critical value of the sensor was calculated to be ΔI = 5.36 μA, that is, the sample was considered to be RV NP antibody positive when ΔI ≥ 5.36 μA, and was considered to be RV NP antibody negative when ΔI ≥ 5.36 μA.

[0054] Table 2. Results of ELISA kit test on clinical samples of rabies

[0055]

[0056] Using differential pulse voltammetry (DPV), the RV NP antibody was tested from low to high concentrations, and the current changes were recorded. It can be seen that the peak current decreases with the increase of RV NP antibody concentration until it reaches saturation. Sensitivity experiment results ( Figure 7 , Figure 8 ), the current change decreased after 500ng / ml, indicating that it has a good linear relationship in the range of 1pg / ml-500ng / ml. According to LOD=3.3*δ / S, where δ is the standard deviation of the response value and S is the slope of the standard curve, the detection limit is calculated to be 2.29pg / ml.

[0057] (2) Repeatability test

[0058] Select the same glassy carbon electrode, modify it with composite materials, fix RV NP antigen, block it with 5% skim milk powder blocking solution, and detect different concentrations of RV NP antibody results under the same assay conditions; select 5 different glassy carbon electrodes, modify them with composite materials, fix RV NP antigen, block them with 5% skim milk powder blocking solution, and detect the same concentration of RV NP antibody under the same assay conditions. Record the data to determine the repeatability effect.

[0059] In order to study the repeatability, the same glassy carbon electrode was used to modify the same composite material, and different concentrations of RV NP antibody were tested under the same measurement conditions. The error bars showed that the currents generated were basically the same ( Fig. 9 ), the error is small; five different glassy carbon electrodes were selected to modify the same composite material, and the same concentration of RV NP antibody was detected under the same measurement conditions. The results showed that the current generated was basically the same ( Fig.10 ), indicating that the biosensor prepared by this method has good reproducibility.

[0060] (3) Stability test

[0061] Three glassy carbon electrodes were modified with AgNPs@Co(II)MOFs@PtNPs composite materials to immobilize rabies antigens. After blocking with 5% skim milk powder blocking solution, stability DPV tests were performed on rabies antibodies of the same concentration. The prepared biosensor was naturally dried and stored at -20°C. The test was performed once at 1d, 3d, 5d, 7d, 14d and 21d, and the data were recorded to determine the stability effect. The results are shown in Fig.11 As shown, the results show that the current generated by the sensor changes little over time, indicating that the sensor has good stability and can be used in the detection of clinical samples.

[0062] (4) Specificity detection

[0063] On the working electrode where RV NP antigen has been fixed and sealed, different antibodies such as Toxoplasma gondii antibody (TGAb), foot-and-mouth disease antibody (FMDV Ab), Brucella antibody (LPS Ab), canine distemper antibody (CDV Ab), and rabies N protein antibody (RV NP Ab) are used to react with the sensor and record the detection data to analyze the sensor specificity. Specific experiments were conducted on TG, FMDV, LPS, CDV, and RV NP antibodies to determine cross-reactivity. The results are shown in Figure 2. Fig.12 As shown. The experimental results show that after skimmed milk powder is blocked, the antigen reacts most strongly with the RV NP antibody, with an average peak current change of 24.3μA. The average peak current changes of other samples are 5.3μA, 4.1μA, 5.1μA, and 8.6μA, respectively, indicating that the sensor has good specificity. The sensor does not react to other non-target antigens (except for CDV, which has a trace reaction, but can also be clearly distinguished from the target antibody). It has good selectivity for samples containing target antibodies.

[0064] (5) Clinical testing

[0065] The developed electrochemical sensor and commercially available ELISA kit were used to analyze 20 clinical inactivated dog sera, with 3 parallel controls for each sample to evaluate its previous clinical application value. The RV NP antigen was fixed on the GCE and blocked with 5% skim milk powder blocking solution. Then, 20 groups of rabies clinical samples were tested separately, with 3 parallel controls for each group, and clinical testing was performed using DPV. The data were recorded and the results of the two methods were analyzed. The results are shown in Table 3. The developed electrochemical detection results showed ( Fig.13 ), among these serum samples, 10 were RN NP antibody positive serum samples, and the detection current changes were 43.6μA, 37.2μA, 33.8μA, 37.8μA, 37.0μA, 44.2μA, 34.6μA, 37.5μA, 34.9μA, 34.7μA; 10 were RV-NP antibody negative serum samples, and the detection current changes were 2.5μA, 3.0μA, 2.6μA, 2.9μA, 1.6μA, 2.2μA, 4.6μA, 2.7μA, 3.2μA, 3.4μA. There was a significant difference between the positive and negative serum samples, p<0.0001. Among the 20 serum samples detected, 20 serum samples showed consistent results by the two methods (10+ / 10-), with a consistency of 100% (Kappa=1.00). According to the statistical analysis results, the developed electrochemical sensor showed high consistency with the commercially available ELISA kit, and there was no significant difference between the two kits (Kappa>0.4) (Table 4). In summary, the developed electrochemical sensor has good sensitivity and specificity, has high consistency with the commercially available ELISA kit, and can be used for clinical detection.

[0066] Table 3. Results of ELISA kit for rabies clinical sample serum

[0067]

[0068] Table 4. Comparison of the electrochemical sensor developed by testing clinical canine serum samples with commercially available ELISA kits

[0069]

[0070] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. AgNPs@Co(II)MOFs@PtNPs nanocomposite material, characterized by: The AgNPs@Co(II)MOFs@PtNPs nanocomposite material is prepared by a mixed solvothermal method to prepare Co(II)MOFs@PtNPs, and then AgNPs are adsorbed on the surface of Co(II)MOFs@PtNPs to form the AgNPs@Co(II)MOFs@PtNPs nanocomposite material.

2. The AgNPs@Co(II)MOFs@PtNPs nanocomposite material according to claim 1, characterized in that: The preparation method of the Co(II)MOFs@PtNPs is as follows: first, a sodium citrate aqueous solution is slowly added to a solution containing H2 PtCl6, and the solution is reacted until it turns dark brown to obtain PtNPs with a size of 250 nm, and then the synthesized PtNPs are added to a mixture containing DMF and ethanol, and then a DMF solution containing CoSO4·7H2O and NH2-H2BDC is added, ultrasonic treatment is performed for 30 minutes, heating is performed at 100°C for 36 hours, and the product is collected by centrifugation to obtain Co(II)MOFs@PtNP.

3. The AgNPs@Co(II)MOFs@PtNPs nanocomposite material according to claim 1, characterized in that: The AgNPs are adsorbed on the surface of Co(II)MOFs@PtNPs by adding AgNPs with an average size of 500 nm to Co(II)MOFs@PtNPs, stirring the reaction for 12 hours, and centrifuging the mixture to obtain the AgNPs@Co(II)MOFs@PtNPs nanocomposite material.

4. Use of the AgNPs@Co(II)MOFs@PtNPs nanocomposite material according to any one of claims 1 to 3 in the preparation of an electrochemical biosensor.

5. An electrochemical biosensor comprising the AgNPs@Co(II)MOFs@PtNPs nanocomposite material according to any one of claims 1 to 3, characterized in that: After the electrochemical biosensor is cleaned by the glassy carbon electrode, the glassy carbon electrode rod is grinded in sequence with a-alumina polishing powder with a particle size of 1.0 μm, 0.5 μm, and 0.05 μm and water. After washing with water, the ultrasonically treated AgNPs@Co(II)MOFs@PtNPs composite material suspension is dropped into the center of the glassy carbon electrode rod and dried to obtain the AgNPs@Co(II)MOFs@PtNPs working electrode.

6. An electrochemical workstation constructed using the electrochemical biosensor according to claim 5.

7. The method for detecting rabies antibodies using the electrochemical biosensor according to claim 5, characterized in that: Rabies nucleoprotein antigen was added to the electrochemical biosensor. The carboxyl group of the nucleoprotein antigen underwent dehydration condensation with the hydroxyl group on the AgNPs@Co(II)MOFs@PtNPs material and was fixed to the electrode. Skim milk powder solution was used as a blocking liquid to block the unbound active sites. The sample to be tested was then placed incubated and rapid detection of rabies antibodies was achieved based on the induced current on the electrode.